Enhancement of Anticancer Activity of N(4)1-(2-Pyridyl)piperazinyl 5-Nitroisatin Thiosemicarbazone on Chelation with Copper(II) - Kumar Singh, Narendra; Shrestha, Smriti; Shahi, Nerina; Kumar Choudhary, Ravinder; A. Kumbhar, Anupa; Raj Pokharel, Yuba; Nath Yadav, Paras (Asian Journal of Chemistry, 2021)
5-Nitroisatin-4-(1-(2-pyridyl)piperazinyl)-3-thiosemicarbazone (Nitistpyrdlpz) and its Cu(II) complex were synthesized and characterized by CHN and thermal analysis and spectroscopic measurements viz. UV-vis, FTIR, 1H NMR, 13C NMR, ESI-HRMS, PXRD and EPR. In the complex, copper(II) ion is coordinated by terdentate thiosemicarbazone anion and one chloride ion in a distorted square planar geometry. The synthesized compounds against breast cancer cell lines; MCF-7 and MDA-MB-231 and epidermoid carcinoma; A431 showed that the complex contributed to reduce the percentage of cell viability toward all the tested cell lines but remarkable contribution toward MDA-MB-231 cell line. The IC50 of the complex and free ligand was found in the range of IC50 0.85-1.24 μM and IC50 3.28-3.53 μM, respectively. Among those cell lines, the complex may be the better anticancer agent toward MDA-MB-231 because of its action at micromolar concentration (IC50 0.85 μM).